Skandinavia sett fra Nürnberg 1493: Skildringen av Danmark, Sverige og Norge i Hartmann Schedels Liber chronicarum - Karlsen, Espen (Nordlit, 2014)
Scandinavia seen from Nürnberg 1493: The depiction of Denmark, Sweden and Norway in the Liber chronicarum by Hartmann Schedel. The present paper provides an edition with facing translation into Norwegian of the passage on Scandinavia in Hartmann Schedel’s Liber chronicarum, printed by Anton Koberger at Nuremberg in 1493. The text and translation is accompanied by reproductions of two maps included in the Liber chronicarum and a facsimile of the passage on Scandinavia. To the translation are added elucidating notes.